2013
DOI: 10.5430/afr.v2n2p69
|View full text |Cite
|
Sign up to set email alerts
|

The Propensity to Trust Others: Gender and Country Differences

Abstract: Our research examines the level of individual trust in others, which is an important issue because it essentially determines the level of additional work that must be done by auditors to make their audit decision. This study includes the responses of 315 accounting students from Afghanistan, Australia, Nepal, and the United States. It then examines whether levels of trust vary by country. Our data indicate that students from both Australia and Nepal had significantly different levels of trust than the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In the context of CC, gender differences have been established in various contexts such as travel (Goel and Haldar, 2020;Lindblom and Lindblom, 2017), tourism (Fondevila-Gasc on et al, 2019), consumption of luxury products (Jain and Mishra, 2020) and bicycle-sharing (Shao et al, 2020). Several studies have also reported gender differences in collaborative consumption driving forces like trust (Shrestha et al, 2013), hedonic motives, and sustainability motives (Tuncer et al, 2005;Bloodhart and Swim, 2020). Thus, it is hypothesized that:…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In the context of CC, gender differences have been established in various contexts such as travel (Goel and Haldar, 2020;Lindblom and Lindblom, 2017), tourism (Fondevila-Gasc on et al, 2019), consumption of luxury products (Jain and Mishra, 2020) and bicycle-sharing (Shao et al, 2020). Several studies have also reported gender differences in collaborative consumption driving forces like trust (Shrestha et al, 2013), hedonic motives, and sustainability motives (Tuncer et al, 2005;Bloodhart and Swim, 2020). Thus, it is hypothesized that:…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…TeamTurst : In Parsons' viewpoint, the confidence is the agent of making unity, stability, cohesion and order. Confidence makes this believe among people that other discard their interest for reaching a group achievement [6]. Studies that performed about technology teams show that confidence results to team efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that performed about technology teams show that confidence results to team efficiency. Shearing the goals, mutual confidence along with respect, clearness in roles limits and individual responsibilities result to a high level of communication in team and finally increase the team confidence [6]. Confidence is a concept that is used differently in various applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation